Experience of variety examination carrying out in Federal Republic of Germany - О. І. Завальнюк; Т. О. Бобир (Plant Varieties Studying and Protection)
In the article was analyzed the system of organization variety examination in one of the most economic development state-member of Union for plant varieties of Plants - Federal Republic of Germany. The structure of administrative authority of plant variety protection - Bundessortenamt and variety testing station enlightened, suggested specific economic indices that could be an example for formation and development national breeding and seed production.